Efficacy of Combined Encorafenib and Binimetinib Treatment for Erdheim–Chester Disease Harboring Concurrent BRAFV600E and KRASG12R Mutations: A Case Report - Yuto Hibino; Rika Sakai; Hiroyuki Takahashi; Takaaki Takeda; Natsuki Hirose; Mayumi Tokunaga; Kota Washimi; Tomoyuki Yokose; Rika Kasajima; Yukihiko Hiroshima; Yohei Miyagi; Hideaki Nakajima (Cancer Reports)
ABSTRACT Background Erdheim–Chester disease (ECD) is a rare form of non‐Langerhans cell histiocytosis with diverse clinical manifestations, often associated with mutations in the mitogen‐activated protein kinase/extracellular signal‐regulated kinase (MAPK/ERK) pathway. BRAF and KRAS mutations, which are driver mutations of oncogenes, participate in the same signaling pathway (MAPK/ERK pathway) and are usually mutually exclusive. We report a case of ECD with concurrent BRAFV600E and KRASG12R mutations treated using BRAF and MEK inhibitors. Case A 70‐year‐old man was referred to our hospital with a mesenteric nodal lesion on computed tomography scan. The patient experienced symptoms consistent with ECD, including central diabetes insipidus. Biopsy revealed histiocytes positive for CD68 and CD163, negative for S100, CD1a, and CD21. Liquid‐based comprehensive genomic profiling and tissue‐based cancer gene panel test identified BRAFV600E and KRASG12R mutations with different variant allele fraction. Additional immunohistochemistry with an antibody specific to mutant BRAFV600E protein stained some proliferating histiocytes, consistent with ECD. Based on the genomic profiling results, we hypothesized that there was a coexistence of a clone harboring BRAFV600E and another clone harboring KRASG12R, and planned a combination therapy with BRAF and MEK inhibitors targeting each clone, respectively. The patient received oral encorafenib at 100 mg once daily and oral binimetinib at 15 mg twice daily. The combination therapy resulted in rapid resolution of symptoms and significant improvement in imaging findings. Conclusion This case represents a unique presentation of ECD with concurrent BRAFV600E and KRASG12R mutations. Combination therapy with encorafenib and binimetinib targeting each clone resulted in a remarkable therapeutic effect and was well‐tolerated. This is the first reported case of ECD treated with encorafenib and binimetinib. The combination therapy with BRAF and MEK inhibitors is one of the rational treatment options for cases of ECD with a suspicion of multiple clones.